2022
DOI: 10.1111/mice.12822
|View full text |Cite
|
Sign up to set email alerts
|

Active learning structural model updating of a multisensory system based on Kriging method and Bayesian inference

Abstract: Model updating techniques are often applied to calibrate the numerical models of bridges using structural health monitoring data. The updated models can facilitate damage assessment and prediction of responses under extreme loading conditions. Some researchers have adopted surrogate models, for example, Kriging approach, to reduce the computations, while others have quantified uncertainties with Bayesian inference. It is desirable to further improve the efficiency and robustness of the Kriging-based model upda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…In the field of civil engineering, relevant studies on GP-based active learning are still rare. In recent years, studies (Tomar & Burton, 2021;Yuan et al, 2022) of GP-based active learning in reliability analysis have started to emerge, in which learning functions like expected improvement function (Jones et al, 1998), expected feasibility function (EFF; Bichon et al, 2008) and U function (Echard et al, 2011) have been implemented to quantify the potential contribution of a certain sample point to the improvement of the prediction performance of the surrogate model. Such potential contribution is mainly quantified by the distance of the sample point to the limit state boundary and the uncertainty.…”
Section: Significance Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of civil engineering, relevant studies on GP-based active learning are still rare. In recent years, studies (Tomar & Burton, 2021;Yuan et al, 2022) of GP-based active learning in reliability analysis have started to emerge, in which learning functions like expected improvement function (Jones et al, 1998), expected feasibility function (EFF; Bichon et al, 2008) and U function (Echard et al, 2011) have been implemented to quantify the potential contribution of a certain sample point to the improvement of the prediction performance of the surrogate model. Such potential contribution is mainly quantified by the distance of the sample point to the limit state boundary and the uncertainty.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…These learning functions are built to achieve the exploitation–exploration tradeoff: (1) “exploitation” means that samples located near the limit state will be preferred; (2) “exploration” means that samples with high uncertainty will be preferred. The exploitation–exploration tradeoff guarantees that a surrogate model for reliability analysis can be obtained to achieve high accuracy within only dozens of learning iterations (Tomar & Burton, 2021; Yuan et al., 2022). However, as this paper aims to predict the EAS evolution over a certain time range (0∼672 h), the main problem is a global prediction rather than a local prediction that only focuses on a certain boundary (i.e., a limit state).…”
Section: Ael Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining such models with kriging methods (Yuan et al., 2023), machine learning algorithms, or neural networks to build response surfaces could significantly improve the existing optimization and structural monitoring methods. Modal and push‐over analyses are already used with machine learning algorithms that are supplied by measured data for damage detection (Ozdaghli & Koutsoukos, 2019; Wen et al., 2023) and structural health monitoring (Hwang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Various dynamic response characteristics have been estimated in prior work, including bridge frequency (Sitton, Rajan, et al, 2020;Sitton, Zeinali, et al, 2020;Yang et al, 2004) and bridge mode shapes (Malekjafarian & O'Brien, 2017b;O'Brien & Malekjafarian, 2016;Yang et al, 2014). These dynamic response characteristics may be used for model updating (Yuan et al, 2023), system identification (O'Brien et al, 2014), damage identification (Sitton, 2023), and damage characterization (Khorram et al, 2012). Comprehensive reviews of research on bridge dynamic response extraction using passing vehicles can be found in Malekjafarian et al (2015), Zhu and Law (2015), , and Wang et al (2022).…”
Section: Introductionmentioning
confidence: 99%